Recent Developments in Nano-Drug Delivery Systems Loaded by Phytochemicals for Wound Healing - Mirrezaei, Neda; Yazdian-Robati, Rezvan; Oroojalian, Fatemeh; Sahebkar, Amirhossein; Hashemi, Maryam (Mini Reviews in Medicinal Chemistry, 2020)
Wound healing is a multi-stage process during which a cascade of molecular and cellular events collaborate to restore the damaged tissue to its healthy state. The inability of the available therapies to effectively heal the wounds has imposed major problems on healthcare systems. Therefore, developing novel therapeutic modalities capable of enhancing wound healing process with no/or limited scar formation is of more importance. Different studies have investigated the potential of phytochemicals on the wound healing process. They have shown to exert anti-inflammatory, antioxidant, and antibacterial activities as well as promoting collagen synthesis and deposition, leading to enhancing wound healing. Nanotechnology, as an applicable knowledge, has provided versatile means to improve the efficiency and effectiveness of wound treatment. The application of nanoparticles has conferred various advantages in the field of wound treatment. They protect the therapeutics from degradation, release the cargo in a controlled fashion, possess healing properties, and can act as extracellular matrix (ECM) mimic. In this review, we discuss the naturally-occurring compounds with wound healing properties and their nano-formulation for skin wound therapy.
Keywords: Wound healing